Vitamin D deficiency and insufficiency in a population cohort from Pernambuco, Brazil (Research, Society and Development, 2022)
Vitamin D plays an important role in immunity and its deficiency or insufficiency (hypovitaminosis D) may be related to the increased prevalence of autoimmune diseases. In a retrospective cohort study with single samples, drawn from a public hospital database, the vitamin D profile of a population was verified. A total of 2,977 patients from 127 municipalities in Pernambuco, Brazil participated in the study. In 12.6% of the municipalities normal means of vitamin D were found (D≥30ng/ml) and in 65.6% deficient means (D